Analyse de sensibilite locale : modele et validation - Ortola, Sophie; Ghouali, Amine; Oster, Alain; Duvaut, Georges (European Journal of Computational Mechanics, 1997)
Shape optimization needs rigorous calculs of sensibilities. Our local sensibility analysis is based on a differentiation of the local equations of the studied problem. This method allows to construct an associated problem, of which solutions are the researched sensibilities. This method is here explained with a simpled problem called << model problem », and then applied on a Dirichlet problem in an ellipsoill domain. When the ellipsoill boundary is perturbed, sensibilities of theses solutions are calculated analytically and numerically by finite element method. Confrontation of both results shows the validity and accuracy of the proposed local analysis sensibility method.